Rain Man

Calculus Level 3

lim n ( 1 n + 1 n + 1 + 1 n + 2 + + 1 4 n ) = ? \lim_{n \to \infty} \bigg ( \frac 1 n + \frac 1 { n+1} + \frac 1 {n+2} + \ldots + \frac 1 { 4n} \bigg ) = \ ?

For more problems refer to the set Calculus Challenges .
ln ( 6 ) \ln(6) ln ( 5 ) \ln(5) ln ( 4 ) \ln(4) ln ( 1 ) \ln(1) ln ( 2 ) \ln(2) ln ( 3 ) \ln(3) ln ( 7 ) \ln(7)

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Varun Gudibanda
Mar 30, 2015

First off, I'd like to say that I liked this problem quite a lot, which is what has compelled me to write this solution. Well done sir.

lim n k = 0 3 n 1 n + k = lim n 1 n k = 0 3 n 1 1 + k n \lim _{ n\rightarrow \infty }{ \sum _{ k=0 }^{ 3n }{ \frac { 1 }{ n+k } } = } \lim _{ n\rightarrow \infty }{ \frac { 1 }{ n } \sum _{ k=0 }^{ 3n }{ \frac { 1 }{ 1+\frac { k }{ n } } } }

Then I let k n = x k \frac{k}{n} = x_k

lim n 1 n k = 0 3 n 1 1 + x k = 0 3 1 1 + x = ln 4 \lim _{ n\rightarrow \infty }{ \frac { 1 }{ n } \sum _{ k=0 }^{ 3n }{ \frac { 1 }{ 1+{ x }_{ k } } } =\int _{ 0 }^{ 3 }{ \frac { 1 }{ 1+x } =\ln { 4 } } }

For more information on this method of finding the limit, search "Playing with Integrals" in the Brilliant search.

Wow, very nice solution. Great job turning a discrete set into a continuous set via integrals. Very good understanding and use of integrals.

Aditya Gudibanda - 3 years, 9 months ago
Aareyan Manzoor
Apr 11, 2015

let H n = n t h h a r m o n i c H_n= nth\quad harmonic then the expression equals lim n ( H 4 n ) lim n ( H n 1 ) \lim_{n\rightarrow\infty} (H_{4n})-\lim_{n\rightarrow\infty} (H_{n-1}) = lim n ( H 4 n ln ( 4 n ) ) lim n ( H n 1 ln ( n 1 ) ) + lim n ( ln ( 4 n ) ln ( n 1 ) ) =\lim_{n\rightarrow\infty} (H_{4n}-\ln(4n))-\lim_{n\rightarrow\infty} (H_{n-1}-\ln(n-1))+\lim_{n\rightarrow\infty} (\ln(4n)-\ln(n-1)) we use the fact that lim n ( H n ln ( n ) ) = γ \lim_{n\rightarrow\infty} (H_{n}-\ln(n))=\gamma where γ \gamma is the Euler–Mascheroni constant. (http://en.wikipedia.org/wiki/Euler%E2%80%93Mascheroni_constant) the limit translates to γ γ + ln ( 4 ) + ln ( lim n ( n n 1 ) ) = ln ( 4 ) \gamma-\gamma+\ln(4)+\ln(\lim_{n\rightarrow\infty}(\dfrac{n}{n-1}))=\boxed{\ln(4)}

This is (basically) how I solved it, too!

Akiva Weinberger - 6 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...